2019
DOI: 10.1002/ejoc.201801363
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Asymmetric Decarboxylative Allylation of Azlactone Enol Carbonates: Fast Access to Enantioenriched α‐Allyl Quaternary Amino Acids

Abstract: We report a fast protocol for the synthesis of enantioenriched quaternary 4‐allyl oxazol‐5‐ones. The key step is a Pd‐catalyzed enantioselective Tsuji allylation of azlactone allyl enol carbonates, which can be easily prepared starting from racemic α‐amino acids. The use of (R,R)‐DACH‐phenyl Trost chiral ligand allowed the attainment of the allylated derivatives in very good yields (83–98 %) and with ee up to 85 %. Scaling up the allylation protocol to gram quantities did not affect the yields end ee values. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Shibasaki, Noda, and later Stoltz utilized the DAAA reaction as the key enantiodetermining step in the development of quaternary β 2,2 -amino acids ( Schemes 217 and 228 ). Colombo also applied this method to the enantioselective synthesis of quaternary α 2,2 -amino acids, 608 using azlactone enol carbonates as substrates, which can be accessed in 33% to 89% overall yield from commercially available tertiary amino acids in three steps ( Scheme 229 ). Among the range of ligands tested, Trost’s ligand ( R , R )-Ph-DACH gave the highest enantioselectivity (70% ee ) for the phenylglycine-derived model substrate.…”
Section: Asymmetric Decarboxylative Allylic Substitutionmentioning
confidence: 99%
“…Shibasaki, Noda, and later Stoltz utilized the DAAA reaction as the key enantiodetermining step in the development of quaternary β 2,2 -amino acids ( Schemes 217 and 228 ). Colombo also applied this method to the enantioselective synthesis of quaternary α 2,2 -amino acids, 608 using azlactone enol carbonates as substrates, which can be accessed in 33% to 89% overall yield from commercially available tertiary amino acids in three steps ( Scheme 229 ). Among the range of ligands tested, Trost’s ligand ( R , R )-Ph-DACH gave the highest enantioselectivity (70% ee ) for the phenylglycine-derived model substrate.…”
Section: Asymmetric Decarboxylative Allylic Substitutionmentioning
confidence: 99%
“…In fact, the separation and purification of azlactone substrates are a relatively tedious operation during their preparation . In order to avoid this tedious operation and conveniently use this kind of compounds in organic synthesis, we attempted to develop a one-pot protocol to synthesize the 4,5-dihydropyridazin-3­(2 H )-ones by using the in situ formed azlactones and the in situ generated azoalkenes.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, Colombo's group reported that the reaction between azlactones ( 234 ) and allyl chloroformates enabled the access to stable allyl enol carbonates ( 235 ) . These intermediates were then submitted to an enantioselective Pd‐catalyzed Tsuji decarboxylative allylation, affording the desired 4‐allyl oxazol‐5‐ones ( 236 ) in good to excellent yields (up to 98 %) and low to good enantioselectivities (ranging from 30 to 85 % ee ) (Scheme A).…”
Section: Conjugate Additions and Other Enolate‐mediated Reactionsmentioning
confidence: 99%